Aggressive posterior retinopathy of prematurity classification, based on clinical and morphometric disease features - A. V. Tereshchenko; Yu. A. Belyy; I. G. Trifanenkova; M. S. Tereshchenkova (Oftalʹmologiâ, 2014)
Based on dynamic monitoring of 133 premature infants (266 eyes) with aggressive posterior retinopathy of prematurity (ROP), digital retinoscopy and computer morphometry the disease clinical and morphometric features were revealed and systematized, and their consecutive replacement was fixed. As a result the separate classification of aggressive posterior disease was worked up. In ag- gressive posterior ROP course the next consecutive stages were marked out: subclinical, early clinical appearances stage, manifesta- tion stage, developed, advanced and terminal stages. the peculiarity of early clinical appearances stage and manifestation stage is thepresence of types: favourable and unfavourable.